Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Controls on timescales of soil organic carbon persistence across sub‐Saharan Africa - Sophie F. von Fromm; Sebastian Doetterl; Benjamin M. Butler; Ermias Aynekulu; Asmeret Asefaw Berhe; Stephan M. Haefele; Steve P. McGrath; Keith D. Shepherd; Johan Six; Lulseged Tamene; Ebagnerin J. Tondoh; Tor‐Gunnar Vågen; et al. (Global Change Biology, 2024)
Given the importance of soil for the global carbon cycle, it is essential to understand not only how much carbon soil stores but also how long this carbon persists. Previous studies have shown that the amount and age of soil carbon are strongly affected by the interaction of climate, vegetation, and mineralogy. However, these findings are primarily based on studies from temperate regions and from fine‐scale studies, leaving large knowledge gaps for soils from understudied regions such as sub‐Saharan Africa. In addition, there is a lack of data to validate modeled soil C dynamics at broad scales. Here, we present insights into organic carbon cycling, based on a new broad‐scale radiocarbon and mineral dataset for sub‐Saharan Africa. We found that in moderately weathered soils in seasonal climate zones with poorly crystalline and reactive clay minerals, organic carbon persists longer on average (topsoil: 201 ± 130 years; subsoil: 645 ± 385 years) than in highly weathered soils in humid regions (topsoil: 140 ± 46 years; subsoil: 454 ± 247 years) with less reactive minerals. Soils in arid climate zones (topsoil: 396 ± 339 years; subsoil: 963 ± 669 years) store organic carbon for periods more similar to those in seasonal climate zones, likely reflecting climatic constraints on weathering, carbon inputs and microbial decomposition. These insights into the timescales of organic carbon persistence in soils of sub‐Saharan Africa suggest that a process‐oriented grouping of soils based on pedo‐climatic conditions may be useful to improve predictions of soil responses to climate change at broader scales.

Impact of dairy farms on groundwater quality in a productive basin in the northeast of the Pampean Plain, Argentina - F. Cellone; L. Santucci; G. Borzi; C. Tanjal; C. Di Lello; L. Butler; J. Córdoba; L. Lamarche; J. Galliari; E. Melendi; M.I. Delgado; E. Carol (Groundwater for Sustainable Development, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

Application of multi-criteria decision analysis to assess sampling strategies in eutrophic urbanized waterbodies - J. Abbatangelo; A. Byrne; J. F. Butler; J. M. Wilson (Environmental Monitoring and Assessment, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Biophysical connectivity explains population genetic structure in a highly dispersive marine species - Nathan K. Truelove; Andrew S. Kough; Donald C. Behringer; Claire B. Paris; Stephen J. Box; Richard F. Preziosi; Mark J. Butler (Coral Reefs, 2017)

Development and testing of a micro wind tunnel for on-site wind erosion simulations - Craig L. Strong; John F. Leys; Mike R. Raupach; Joanna E. Bullard; Hélène A. Aubault; Harry J. Butler; Grant H. McTainsh (Environmental Fluid Mechanics, 2016)

Depleted Uranium Toxicity, Accumulation, and Uptake in Cynodon dactylon (Bermuda) and Aristida purpurea (Purple Threeawn) - Afrachanna D. Butler; Michelle Wynter; Victor F. Medina; Anthony J. Bednar (Bulletin of Environmental Contamination and Toxicology, 2016)

Family Forest Owners’ Perceptions of Landowner Assistance Programs in the USA: A Qualitative Exploration of Program Impacts on Behaviour - Kyle Andrejczyk; Brett J. Butler; Brenton J. Dickinson; Jaketon H. Hewes; Marla Markowski-Lindsay; David B. Kittredge; Michael A. Kilgore; Stephanie A. Snyder; Paul F. Catanzaro (Small-scale Forestry, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Genetic evidence from the spiny lobster fishery supports international cooperation among Central American marine protected areas - Nathan K. Truelove; Sarah Griffiths; Kim Ley-Cooper; James Azueta; Isaias Majil; Stephen J. Box; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Conservation Genetics, 2015)

Larval Distribution and Behavior of Chrysomya rufifacies (Macquart) (Diptera: Calliphoridae) Relative to Other Species on Florida Black Bear (Carnivora: Ursidae) Decomposing Carcasses - S L Swiger; J A Hogsette; J F Butler (Neotropical Entomology, 2014)

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

Sources of Botrytis cinerea inoculum for flower infection in blackcurrants in New Zealand - K. Boyd-Wilson; F. Obanor; R. C. Butler; P. Harris-Virgin; G. I. Langford; J. T. Smith; M. Walter (Australasian Plant Pathology, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Improving the Performance of the Roundtable on Sustainable Palm Oil for Nature Conservation - WILLIAM F. LAURANCE; LIAN P. KOH; RHETT BUTLER; NAVJOT S. SODHI; COREY J. A. BRADSHAW; J. DAVID NEIDEL; HAZEL CONSUNJI; JAVIER MATEO VEGA (Conservation Biology, 2010)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Regional characterisation of hard‐bottom nursery habitat for juvenile Caribbean spiny lobster (Panulirus argus) using rapid assessment techniques - Rodney D. Bertelsen; Mark J. Butler; William F. Herrnkind; John H. Hunt (New Zealand Journal of Marine and Freshwater Research, 2009)
Shallow, hard‐bottom habitat constitutes approximately 30% of the coastal waters of south Florida, United States, yet it is a chronically understudied feature of the marine seascape in this region. In this study, we characterised the general biogeographic and structural features of shallow benthic hard‐bottom communities in the Florida Keys, and related those to the abundance of juvenile Caribbean spiny lobster (Panulirus argus) , the target of one of Florida's most economically valuable fisheries. We used rapid assessment techniques to survey more than 100 hard‐bottom sites in the Florida Keys to estimate the percentage bottom coverage of vegetation (seagrass and macroalgae) and the abundance of sponges, octocorals, hard corals, and other crevice‐bearing structures, as well as the abundance of juvenile lobsters. Using a multivariate statistical approach, we evaluated the relationship between habitat and size‐specific juvenile lobster abundance and quantitatively verified the existence of six generally accepted biogeographic subregions. Although the types of hard‐bottom shelters used by juvenile lobsters varied somewhat among these subregions, in all regions, branching‐candle sponges and octocorals were under‐used by lobsters, whereas loggerhead sponges, coral heads, and solution holes were over‐used (i.e., used more frequently than expected based on their availability). There was also an ontogenetic transition in the shelter preference of juvenile lobsters; small juveniles tended to occupy a variety of sponges, whereas large juveniles preferred hard structures such as coral heads and solution holes. This study yields the first quantitative biogeographic description of hard‐bottom communities of the Florida Keys, and confirms the suspected relationship between the structural features of hard‐bottom habitat and the value of these communities as nurseries for juvenile spiny lobster.

Is seagrass an important nursery habitat for the Caribbean spiny lobster, panulirus argus , in Florida? - Donald C. Behringer; Mark J. Butler; William F. Herrnkind; John H. Hunt; Charles A. Acosta; William C. Sharp (New Zealand Journal of Marine and Freshwater Research, 2009)
Caribbean spiny lobster (Panulirus argus) settle preferentially in macroalgal‐covered hard‐bottom habitat, but seagrass is more prevalent in Florida (United States) and the Caribbean, so even low settlement of lobsters within seagrass could contribute substantially to recruitment if post‐settlement survival and growth were high. We tested the role of seagrass and hard‐bottom habitats for P. argus recruitment in three ways. We first explored possible density‐dependent regulation of early benthic juvenile lobster survival within cages deployed in seagrass and hard‐bottom habitats. Second, we compared settlement and survival of P. argus in both habitats, by comparing the recovery of microwire‐tagged early benthic juveniles from patches of seagrass and hard‐bottom. Finally, we assessed the relative abundance of juvenile lobsters in each habitat by deploying artificial structures in seagrass sites and compared these data with data from similar deployments of artificial structures in hard‐bottom habitat in other years. More early benthic juvenile lobsters were recovered from cages placed in hard‐bottom than in seagrass, but mortality of the early benthic life stage was high in both habitats. In regional surveys, the mean number of lobsters recovered from artificial shelters deployed within seagrass was lower than in any year that we sampled hard‐bottom, indicating that fewer lobsters reside naturally in seagrass, particularly large juveniles >40 mm carapace length. The greater abundance (and likely survival) of juvenile P. argus that we observed in hard‐bottom habitat as opposed to seagrass, combined with previous studies demonstrating that postlarval P. argus are attracted to, settle in, and metamorphose more quickly in red macroalgae, confirm that macroalgae‐dominated hard‐bottom habitat appears to be the preferred and more optimal nursery for Caribbean spiny lobster.

Biogeography of seed‐dispersal syndromes, life‐forms and seed sizes among woody rain‐forest plants in Australia's subtropics - D. W. Butler; R. J. Green; D. Lamb; W. J. F. McDonald; P. I. Forster (Journal of Biogeography, 2007)
Aim To enhance our understanding of the evolutionary interactions between seed‐dispersal syndromes, life‐forms, seed size, and habitat characteristics by studying their association with the regional‐scale distributions of subtropical rain‐forest plants in the context of climatic gradients. Location South‐east Queensland, subtropical eastern Australia (152° E, 26° S). Methods We classified 250 rain‐forest sites into six floristic site‐groups based on their woody plant composition. The resulting classification was strongly associated with variation in rainfall. The distribution of species across the floristic site‐groups was used to assign 568 species to seven habitat classes (one class for ‘widespread’ species, with all other species classified according to the site‐group within which they were most frequent). Species were also classified for three other categorical life‐history factors: three dispersal syndromes based on diaspore morphology (fleshy, wind‐assisted, and unadorned); four life‐forms (trees, shrubs and small trees, tall climbers, and short and shrubby climbers); and four seed‐diameter classes ( Results Across the rain forests of south‐east Queensland, the proportion of species with fleshy diaspores or of large stature increases with rainfall. High‐rainfall sites also have larger average seed sizes, but the difference in average seed size between high‐ and low‐rainfall sites is small compared with variation within sites. Among species, those with fleshy fruit tend to have larger seeds and to favour high‐rainfall sites. Very few small trees produce diaspores adapted for wind‐assisted dispersal. On average, species with unadorned diaspores have smaller seeds than those with fleshy diaspores. However, within sites, species with unadorned and fleshy diaspores have similar average seed sizes, and some species with unadorned diaspores from high‐rainfall habitats have extremely large seeds. Main conclusions Commonly observed associations between fleshy fruit, larger plants, larger seeds, and productive habitats are apparent within the rain‐forest flora of south‐east Queensland. However, these associations are generally weak and involve complex interactions. For example, the strong tendency for species with fleshy fruit to have larger seeds than those with unadorned diaspores concealed a significant group of species from wetter forests that produce extremely large seeds and unadorned diaspores. The most widespread species in this study tend to be large plants (particularly robust lianes) and to produce fleshy fruit, but they tend not to have relatively large seeds. The association between large seeds, large plants, fleshy fruit and productive habitats is discussed as part of an evolutionary strategy favouring fitness in populations close to carrying capacity. We review some problems with focusing on establishment chances per seed as the driver towards association between large seeds, large plants and productive rain‐forest habitats (the difficult‐establishment hypothesis). Instead we suggest that production of large, short‐lived seeds by long‐lived plants in temporally stable, closed habitats may reflect the limited evolutionary potential for strategies enhancing colonization (e.g. producing large numbers of dormant seeds), thus allowing the establishment benefits of large seeds greater selective influence (the slow‐replacement hypothesis). The association of fleshy fruit with large seeds probably reflects the difficulty of dispersing large seeds by other means (the difficult‐dispersal hypothesis).

Assessment of genetic diversity in isolates of Ciborinia camelliae Kohn from New Zealand and the United States of America - R. F. van Toor; H. J. Ridgway; R. C. Butler; M. V. Jaspers; A. Stewart (Australasian Plant Pathology, 2005)

A direct regional scale estimate of transgene movement from genetically modified oilseed rape to its wild progenitors - M. J. Wilkinson; I. J. Davenport; Y. M. Charters; A. E. Jones; J. Allainguillaume; H. T. Butler; D. C. Mason; A. F. Raybould (Molecular Ecology, 2000)
One of the major environmental concerns over genetically modified (GM) crops relates to transgene movement into wild relatives. The pattern of hybridization ultimately affects the scale and rapidity of ecological change and the feasibility of containment. A new procedure for quantifying hybrid formation over large areas is described. Remote sensing was used to identify possible sites of sympatry between Brassica napus and its progenitor species across 15 000 km 2 of south‐east England in 1998. Two sympatric populations with B. rapa and one with B. oleracea were found over the entire survey area. Every newly recruited plant in these populations in 1999 was screened for hybrid status using flow cytometry and molecular analyses. One hybrid was observed from the 505 plants screened in the B. rapa populations but none of the nine B. oleracea recruits were hybrids. Measures to minimize gene flow are suggested, and a procedure for the post‐release evaluation and containment of GM cultivars is proposed.

Construction of an RFLP linkage map for cultivated sunflower - C. C. Jan; B. A. Vick; J. F. Miller; A. L. Kahler; E. T. Butler III. (Theoretical and Applied Genetics, 1998)